Effect of the ionomers in the electrode on the performance of PEMFC under non-humidifying conditions - Ahn, SY; Lee, YC; Ha, HY; Hong, SA; Oh, IH (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
New electrodes for polymer electrolyte membrane fuel cells (PEMFCs) have been developed to improve the performance of PEMFCs under non-humidifying condition by optimizing electrode composition. The ionomer with a lower equivalent weight (EW 1000) was used in the electrode to enhance the proton conductivity and thus to reduce the ohmic resistance under dry conditions. Though the proton conductivity of the polymer electrolyte was inversely proportional to its equivalent weight, the effect of the EW was more pronounced in the performance of the MEA at low humidity conditions. Performances of the new MEAs were compared with those of conventional MEAs with EW 1100 ionomer by using polarization curves and impedance analysis under various humidity conditions. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: QUANTUM JUMPS; FUEL-CELLS; HUMIDIFICATION; TECHNOLOGY; MEMBRANES; SCIENCE; 1960S